Genome-wide association studies for a comprehensive understanding of the genetic architecture of culm strength and yield traits in rice - Badri, Jyothi; Padmashree, Revadi; Anilkumar, Chandrappa; Mamidi, Akshay; Isetty, Subhakara Rao; Swamy, AVSR; Sundaram, Raman Menakshi (Frontiers in Plant Science, 2024)
Lodging resistance in rice is a complex trait determined by culm morphological and culm physical strength traits and the trait is a major determinant of yield. We made a detailed analysis of various component traits and attempted to derivewith the aim of deriving optimized parameters for measuring culm strength. GBS based GWAS was employed among 181 genotypes for dissecting the genetic control of culm strength traits. The VanRaden kinship algorithm using 6,822 filtered SNPs revealed the presence of two sub-groups within the association panel with kinship value concentrated at <0.5 level indicating greater diversity among the genotypes. A wide range of phenotypic variation and high heritability for culm strength and yield traits was observed over two seasons as reflected in best linear unbiased predictor (BLUP) estimates. Multi-locus model for GWAS resulted in the identification of 15 highly significant associations (p<0.0001) for culm strength traits. Two novel major effect marker trait associations (MTAs) for section modulus and bending stress were identified on chromosomes 2 and 12 with a phenotypic variance of 21.87 and 10.14 % respectively. Other MTAs were also noted in the vicinity of previously reported putative candidate genes for lodging resistance, providing an opportunity for further research on biochemical basis of culm strength. The QTL hot spot identified on chromosome 12 with synergistic association for culm strength trait (section modulus, bending stress and internode breaking weight) and grain number can be considered as a novel genomic region that can serve dual purpose of enhancing culm strength and grain yield. Elite donors in the indica background with beneficial alleles of the identified major QTLs could be a valuable resource with greater significance in practical plant breeding programs focusing on improving lodging resistance in rice.